Eksplorasi etnomatematika terhadap konsep geometri pada struktur bangunan rumah joglo semar tinandhu - Nurkhafifah, Siti; Pailokol, Nilam Sari; Megawanti, Priarti (Himpunan: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2021)
Indonesia has a variety of cultures, one of which is traditional houses. Traditional house architecture not only has a spiritual meaning but also contains educational values, namely those related to mathematics, namely ethnomathematics. The purpose of this study was to examine and describe the ethnomathematical exploration of geometric concepts in the structure of the Joglo Semar Tinandhu house. The method used in this research is the method of studying literature from previous journals and articles. The results of the study describe that there is a geometric concept in the Joglo Semar Tinandhu traditional house consisting of (1) flat shapes, namely square, rectangular, triangle, trapezoidal, rhombus. (2) construct space, namely cubes, blocks, pyramids, and prisms. (3) the concept of congruence and congruence as well as geometric transformation that can be used as an approach to students regarding the concept of geometry.Key Words:Ethnomathematics, Geometric Concepts, Joglo Semar Tinandhu House